From risk to care: the hepatitis C screening and diagnostic cascade in a primary health care clinic in Karachi, Pakistan—a cohort study - Khalid, Gul Ghuttai (Int Health, 2018)
BACKGROUND: In the high-prevalence setting of Pakistan, screening, diagnosis and treatment services for chronic hepatitis C (CHC) patients are commonly offered in specialized facilities. We aimed to describe the cascade of care in a Médecins Sans Frontières primary health care clinic offering CHC care in an informal settlement in Karachi, Pakistan. METHODS: This was a retrospective cohort analysis using routinely collected data. Three different screening algorithms were assessed among patients with one or more CHC risk factors. RESULTS: Among the 87 348 patients attending the outpatient clinic, 5003 (6%) presented with one or more risk factors. Rapid diagnostic test (RDT) positivity was 38% overall. Approximately 60% of the CHC patients across all risk categories were in the early stage of the disease, with an aspartate aminotransferase:platelet ratio index score <1. The sequential delays in the cascade differed between the three groups, with the interval between screening and treatment initiation being the shortest in the cohort tested with GeneXpert onsite. CONCLUSIONS: Delays between screening and treatment can be reduced by putting in place more patient-centric testing algorithms. New strategies, to better identify and treat the hidden at-risk populations, should be developed and implemented.